International spillovers of monetary policy: Evidence from France and Italy - Julia Schmidt; Marianna Caccavaio; Luisa Carpinelli; Giuseppe Marinelli (European Central Bank (ECB), 2018)
In this paper we provide empirical evidence on the impact of US and UK monetary policy changes on credit supply of banks operating in Italy and France over the period 2000-2015, exploring the existence of an international bank lending channel based on the reliance on funding sources located in these two countries or denominated in their currency. We find that US monetary policy tightening leads to a reduction of lending to the domestic economy in both France and Italy, and this is mainly driven by banks that relied more intensely on USD funding markets. Conversely, we find that both French and Italian banks are isolated from UK monetary policy shocks, as most of their UK funding is denominated in Euro, despite being larger than funding from the US.
Keywords: E51; F30; F42; G20; 330; bank lending channel; foreign funding; global banks